Evaluation of the Serum Uric Acid Level as an Early Predictor of Mortality Among the Patients with Myocardial Infarction: A Prospective Study - Lipika Jena; Santosh Singh; Sarthak Nayak; Birasena Behera; Rajashree Panigrahi; Sandeep Panigrahi (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2022)
Background and aim: Myocardial infarction (MI) is one of the most common causes of death through the globe. Serum uric acid (SUA) is elevated in underlying tissue ischemia. This research conducted to establish the association of SUA extents with MI patients admitted to a tertiary care hospital and to compare SUA levels with Killip Classification as an early prognostic marker in these patients. Material and methods: Our study involved 100 consecutive AMI patients and 100 age- and sex-matched controls. SUA levels were estimated on the 0th, 3rd, and 7th days of MI and compared with the Killip class, indicative of the severity of heart failure. SUA was measured by the uricase method. Results: The present study has been undertaken to correlate serum uric acid level as a prognostic marker in patients with myocardial infarction. In myocardial infarction, the higher the uric acid level higher is the risk of mortality. In our study, MI and hypertensive patients had significantly higher SUA levels on days 0, 3, and 7. Also, our study showed SUA levels were significantly larger in patients who belonged to a greater Killip class (Killip III and IV). Among the ten patients who died, eight had SUA levels>7.0 mg/dL during the admission. Among those ten cases, nine patients were in the higher Killip class and one in Killip I class. Conclusions: Patients with a history of MI and hypertensive have higher SUA levels and are in the greater Killip class. A union of Killip class and SUA after AMI is a good predictor of mortality.